Peran Ekonomi Digital Terhadap Kinerja Pasar Modern Di Indonesia - Dhea Isti Riyana; Iva Khoiril Mala; Sutantri Sutantri (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This research aims to find out the role of the digital economy in the performance of modern markets in Indonesia. The method used in this research is a qualitative descriptive method by collecting data from various books and journals whose research focus is the same as the title of the research being studied. The research results show that the digital business economy has provided opportunities for entrepreneurs in the future. By using digital everyone can advance their business and gain profits. With this modern market, consumers will find it easier to access transactions with traders in unlimited areas. However, on the other hand, the modern market also has a negative impact on the Indonesian economy, such as the traditional market ecosystem which will be defeated by the modern market and fraud.